Rabindranath Tagore the poet sublime - Dutta Gupta, Reeta (New Delhi Rupa & Co., 2002)
On life and works of Rabindranath Tagore, 1861-1941; a study.
Keywords: Tagore, Rabindranath -- 1861-1941 -- Criticism and interpretation